Truth and Probability—Ironies in the Evolution of Social Choice Theory - Cheryl D. Block (Washington University Law Quarterly, 1998)
Social choice theory explores the ways in which individual preferences or choices translate into group choices. One of the most devastating discoveries of social choice theory is sometimes known as the "voting paradox," brought back to modem consciousness by economist, Kenneth Arrow, in his famous work entitled Social Choice and Individual Values. Roughly stated, the paradox is that voting in situations involving more than a simple, binary choice will not always reveal the true decision of a decision-making body. The motivation for this Article is to understand how and why, having discovered the voting paradox in 1785, Condorcet actually became a more ardent believer in democratic decision making in later writings until his unfortunate death in 1794. More importantly, this Article examines Condorcet's discovery of the voting paradox in the larger context of his life's work to determine what solutions to the paradox he might have seen that modem social choice theorists and the legal literature have not fully explored. Part II of this Article briefly describes the history and implications of social choice theory and the famous voting paradox. Part III first offers a general picture of Condorcet's life and work. It then explores the connections between the philosophies of Condorcet, Rousseau and the more modem civic republican traditions. Part IV takes a closer look at Condorcet's original decision-making theory. Part V uncovers many civic republican themes within the context of the larger body of Condorcet's work and uses these themes to explore what his work might contribute to the modem discourse.
Keywords: Elections; Public choice theory; Condorcet; Jean-Antoine-Nicolas de Caritat; marquis de; 1743-1794; Social choice; Voting; Kenneth J. Arrow